PENERAPAN METODE INKUIRI DALAM PENINGKATAN PEMBELAJARAN IPA SISWA KELAS IV SEKOLAH DASAR - ROHMAH, ULFATUN (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The application of inquiry method in science learning fourth grade students at Mangli elementary school. This research aims to: (1) improve science learning fourth grade students at Mangli elementary school, (2) describe an increase in science learning fourth grade students at elementary school Mangli. This research was a collaborative classroom action research was conducted in two cycles, each cycle includes the planning, implementation, observation and reflection. The subjects were fourth grade students at elementary school. The results showed that: (1) by applying inquiry method science learning fourth grade students at elementary school be increased, (2) inquiry method can increase the science learning fourth grade students at elementary school with steps which include orientation, formulate problems, formulate hypotheses, collecting data, testing hypotheses, and making conclusions. Keywords: inquiry method, science learning.   Abstrak: Penerapan metode inkuiri dalam pembelajaran IPA siswa kelas IV Sekolah Dasar. Penelitian ini bertujuan untuk: (1) meningkatkan pembelajaran IPA siswa kelas IV SDN Mangli, (2) mendeskripsikan peningkatan pembelajaran IPA siswa kelas IV SDN Mangli. Penelitian ini merupakan Penelitian Tindakan Kelas kolaboratif yang dilaksanakan dalam 2 siklus 1 siklus terdiri dari 3 pertemuan, masing-masing siklus mencakup tahap perencanaan, pelaksanaan, observasi dan refleksi. Subjek penelitian ini adalah siswa kelas IV SDN Mangli. Hasil penelitian ini menunjukkan bahwa: (1) dengan menerapkan metode inkuiri, pembelajaran IPA siswa kelas IV SDN Mangli dapat meningkat, (2) metode inkuiri dapat meningkatkan pembelajaran IPA siswa kelas IV SDN Mangli dengan langkah-langkah yang meliputi orientasi, merumuskan masalah, merumuskan hipotesis, mengumpulkan data, menguji hipotesis, dan merumuskan kesimpulan. Kata Kunci: metode inkuiri, pembelajaran IPA.